(untitled) (Third Sector Social Economic Review, 2018)
Psychological contract breach is an antecedent of a substantial amount of organizational outcomes. Therefore, it is important to identify the factors affecting psychological contract breach perception. In this study, it was investigated that the effect of compulsory citizenship behavior on the psychological contract breach and the moderating role of leader-member exchange in this relationship. Using the cross-sectional design, the data was gathered from 192 participants working in the private sector by convenience method. Correlation and regression analyses were performed to test hypotheses. Results revealed that compulsory citizenship behavior has effect on the psychological contract breach and leader-member exchange moderates this relationship. Managerial implications, limitations and suggestions have been discussed.